ANALISIS FAKTOR YANG MENGHAMBAT DALAM PENANAMAN PENDIDIKAN KARAKTER DISIPLIN PADA SISWA DI SDN 02 SERUT KECAMATAN BOYOLANGU - Moh - Gufron (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
The research objective is to determine the application of the teacher in the cultivation of discipline character education in children, the application of students after instilling character education as well as factors that inhibit the cultivation of discipline character education in students. Discipline character education is compliance with regulations and prevailing norms accompanied by awareness. Various kinds of disciplinary violations, skipping school, not doing the teacher's work, disrupting other classes, cheating, being late, bringing toys to class, fighting with friends. The study was conducted in SDN 02 Serut Kecamatan Boyolangu Kabupaten Tulungagung, the type of research used was descriptive qualitative with methods of collecting data on observation, interviews, documentation, field notes. The process of data analysis through data reduction, data presentation, drawing conclusions. The results of the study of character education planting were carried out through appeals carried out during the Monday flag ceremony and teachers in planting students through an understanding of students about the importance of character education, factors that inhibit from outside and within the family and themselves.